The intention experiment eaudiobook Using your thoughts to change your life and the world. - McTaggart, Lynne (Recorded Books Inc., 2016)
Award-winning science journalist and author Lynne McTaggart invites listeners to take part in the world's largest mind-over-matter experiment in The Intention Experiment. By thinking positively about life and consciousness, people can, in fact, change their lives. "If you want to empower yourself ... read this book."-Deepak Chopra